2012
DOI: 10.1080/01635581.2012.668744
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nutrition Parameters Including Bioelectrical Impedance and Systemic Inflammatory Response With Quality of Life and Prognosis in Patients With Advanced Non-Small-Cell Lung Cancer: A Prospective Study

Abstract: Early identification and treatment of nutritional deficiencies can lead to improved outcomes in the quality of life (QoL) and survival of patients with nonsmall cell lung cancer (NSCLC). Noninvasive techniques are needed to evaluate changes in body composition as part of determining nutritional status. The aim of the study was to evaluate the association of nutritional parameters in health-related quality of life (HRQL) and survival in patients with advanced NSCLC. Chemotherapy-naïve patients with advanced NSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 51 publications
2
119
2
3
Order By: Relevance
“…In a study where albumin NLR and PLR were evaluated, NLR was found to be statistically insignificant as a prognostic factor unlike our study, whereas PLR and serum albumin level was found to have a prognostic significance (Sánchez-Lara et al, 2012).…”
Section: 5473 Basic Laboratory Methods In Determining Prognosis Of Ncontrasting
confidence: 41%
“…In a study where albumin NLR and PLR were evaluated, NLR was found to be statistically insignificant as a prognostic factor unlike our study, whereas PLR and serum albumin level was found to have a prognostic significance (Sánchez-Lara et al, 2012).…”
Section: 5473 Basic Laboratory Methods In Determining Prognosis Of Ncontrasting
confidence: 41%
“…PLR was accepted as an inflammatory marker among other inflammatory parameters, which were used to evaluate the relationship among nutritional and inflammatory parameters with health-related quality of life in advanced stage NSCLC [20]. Mean PLR was estimated as 231.2 ± 162.3 in this study, including 119 NSCLC patients.…”
Section: Resultsmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) are other markers, and some studies have shown elevated NLR or PLR to be a significant prognostic factor in various cancers [4][5][6][7][8][9], including NSCLC [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%